Parental Birth-Related PTSD Symptoms and Bonding in the Early Postpartum Period: A Prospective Population-Based Cohort Study - Stuijfzand, Suzannah; Garthus-Niegel, Susan; Horsch, Antje (Frontiers in Psychiatry, 2020)
The parent-infant bond following childbirth is an important facilitator of optimal infant development. So far, research has mainly focused on mother-infant bonding. Data on fathers are still sparse. Parental mental health may influence mother-infant relations and/or interactions, for example posttraumatic stress symptoms (PTSD). There is evidence that both parents can experience PTSD symptoms following childbirth (PTSD-CB). The aim of this study is to investigate the prospective relationship between parental PTSD-CB symptoms at one month postpartum and perceived parent-infant bonding at three months postpartum, while adjusting for antenatal confounders. A subsample was used for this study (nTotalsample 488, nmothers = 356, nfathers = 132) of an ongoing prospective cohort study. Future parents awaiting their third trimester antenatal appointments at a Swiss university hospital were recruited. Self-report questionnaires assessed PTSD-CB symptoms and psychological distress at one month postpartum, and parent-infant bonding at three months postpartum. Confounders included antenatal PTSD symptoms and social support measured via self-report questionnaires, and gestity and gestational age, extracted from medical records. Using structural equation modelling, the predictive ability of PTSD-CB symptoms at one month postpartum on parent-infant bonding at three months postpartum was assessed for both parents respectively. Maternal PTSD-CB symptoms at one month postpartum were found to be negatively prospectively associated with mother-infant bonding at three months postpartum; however, this effect disappeared after adjusting for psychological distress at one month postpartum. No such effects were found for fathers. There was no evidence of mediation of the relationship between parental PTSD-CB symptoms at one month postpartum and parental-infant bonding at three months postpartum via psychological distress at one month postpartum. However, such a mediation was found for maternal intrusion and hyperarousal symptom subscales. Results expand the current literature on the impact of PTSD-CB on parent-child relations to also include fathers, and to a community sample. Any adverse effects of mental health symptoms on parent-infant bonding were evidenced by three months postpartum only for mothers, not fathers. Our results may inform the development of prevention/intervention strategies.